Atrial Fibrillation in Cancer Patients: Who is at Risk? - Yu. A. Vasyuk; E. Yu. Shupenina; D. A. Vyzhigin; E. O. Novosel; K. V. Gallinger (Столичная издательская компания, 2022)
Cancer is the second leading cause of mortality in the world, second only to cardiovascular diseases. Simultaneously cancer mortality has been steadily decreasing due to the development  of new chemotherapy and targeted  drugs  and the improvement  of existing  treatment protocols.  Improving the prognosis of treatment of cancer patients leads to an unexpected  result - more patients are faced with side effects of cancer treatment. Cardiotoxicity, including  arrhythmia, has  become  a significant  factor  to reduce  the effectiveness  of cancer  patient's  treatment.  Atrial  fibrillation  is frequent  and persistent a rhythm disorder, affecting  all categories  of patients, especially the elderly. An association  between these two conditions  can be expected, considering the fact that in old age the prevalence of malignant neoplasms  and comorbid pathology predisposing to the onset of AF is high. Therefore, AF may be an additional  factor negatively  influencing the prognosis and treatment tactics in patients with malignant neoplasms. A comprehensive search was conducted  using the keywords  "cancer", "atrial fibrillation" and "cardiotoxicity" using the PubMed,  Scopus and Cohrane  databases. We reviewed publications having the relationship between AF and cancer. The literature review considered 61 publications on the prevalence of AF in cancer patients, classification, mechanisms of development, the effect of anticancer drugs and other treatment methods on this group of patients. Analyzed articles include clinical guidelines, consensus  expert opinions,  systematic  reviews,  meta-analyzes, and previously  published  reviews of the literature. The problem of cardiotoxic  complications diagnostics is evaluated separately,  incl. arrhythmias, and their monitoring in cancer patients. Therefore, the direction of medicine named "Cardio-oncology" comes to the fore. Interdisciplinary interaction will allow identify cardiotoxic  manifestations at the subclinical stage and optimize anticancer treatment.